Breaking the sporoderm of Ganoderma lucidum spores by combining chemical reaction with physical actuation. Issue 20 (18th October 2017) - Wang, Jiajia; Ke, Rui; Zhang, Shengyi
Abstract: The hard and indissolvable sporoderm of Ganoderma lucidum spore (GLS) hinders the release of bioactive components that are significant to disease treatment and vitality enhancement. In this paper, a strategy to break sporoderm was proposed, in which the chemical reaction was cooperated with physical actuation (ultrasonication and refrigeration). Dealing with this chemicophysical treatment, the porous sporoderm of GLS was formed, which was confirmed by scanning electron microscope (SEM). The effect factors and mechanism of breaking sporoderm were discussed, and the efficiency of breaking sporoderm was evaluated by detecting the dissolution behaviour of inner triterpenoids in GLS. In addition, aiming to improve the solubility and stability of GLS product, the β-cyclodextrin was used to seal the holes on sporoderm of GLS product. The results show that the developed method is effective and feasible in producing high-bioactive and stable GLS product. Abstract :